(untitled) (International journal of artificial intelligence, 2025)
This article explores the methodological foundations necessary for the formation of functional literacy among students in Uzbek language lessons. The paper emphasizes the importance of functional literacy as a key competency in the modern educational process, focusing on the integration of communicative, cognitive, and pragmatic skills through language instruction. The study presents modern pedagogical approaches and strategies that help develop students’ ability to apply language knowledge in real-life situations.